2023
DOI: 10.1007/s00068-023-02244-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Swedish Trauma Registry (SweTrau)

Abstract: Purpose Validation of registries is important to ensure accuracy of data and registry-based research. This is often done by comparisons of the original registry data with other sources, e.g. another registry or a re-registration of data. Founded in 2011, the Swedish Trauma Registry (SweTrau) consists of variables based on international consensus (the Utstein Template of Trauma). This project aimed to perform the first validation of SweTrau. Methods On-site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…SweTrau is a national quality register established in 2011 using the Utstein Trauma Template for Uniform Reporting of Data following Major Trauma [ 11 ]. The registry is evaluated with good validity [ 12 ]. During the study period, 46 hospitals reported to SweTrau.…”
Section: Methodsmentioning
confidence: 99%
“…SweTrau is a national quality register established in 2011 using the Utstein Trauma Template for Uniform Reporting of Data following Major Trauma [ 11 ]. The registry is evaluated with good validity [ 12 ]. During the study period, 46 hospitals reported to SweTrau.…”
Section: Methodsmentioning
confidence: 99%
“…All traumatic injuries found during the hospital stay are registered. The register has recently been validated and high accuracy, correctness, data completeness, and correlation were reported ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of trauma patients in Sweden are transported to an ED, and severely injured patients are well described in the national trauma registry [ 6 ]. However, a considerable proportion of patients are triaged to a PCC or remain at the scene and receive advice on self-care [ 1 ].…”
Section: Introductionmentioning
confidence: 99%